Randomized control trial of benzydamine HCl versus sodium bicarbonate for prophylaxis of concurrent chemoradiation-induced oral mucositis - Imjai Chitapanarux (2018)
© 2017, Springer-Verlag GmbH Germany. Purpose: The purpose of the study is to compare the efficacy of benzydamine HCl with sodium bicarbonate in the prevention of concurrent chemoradiation-induced oral mucositis in head and neck cancer patients. Methods: Sixty locally advanced head and neck cancer patients treated with high-dose radiotherapy concurrently with platinum-based chemotherapy were randomly assigned to receive either benzydamine HCl or sodium bicarbonate from the first day of treatment to 2 weeks after the completion of treatment. The total score for mucositis, based on the Oral Mucositis Assessment Scale (OMAS), was used for the assessment, conducted weekly during the treatment period and at the fourth week of the follow-up. Pain score, all prescribed medications, and tube feeding needs were also recorded and compared. Results: The median of total OMAS score was statistically significant lower in patients who received benzydamine HCl during concurrent chemo-radiotherapy (CCRT) than in those who received sodium bicarbonate, (p value < 0.001). There was no difference in median pain score, (p value = 0.52). Nineteen percent of patients in sodium bicarbonate arm needed oral antifungal agents whereas none in the benzydamine HCl arm required such medications, (p value = 0.06). Tube feeding needs and the compliance of CCRT were not different between the two study arms. Conclusions: For patients undergoing high-dose radiotherapy concurrently with platinum-based chemotherapy, using benzydamine HCl mouthwash as a preventive approach was superior to basic oral care using sodium bicarbonate mouthwash in terms of reducing the severity of oral mucositis and encouraging trend for the less need of oral antifungal drugs.